Financial condition and product market cooperation - Gustafson, Matthew T.; Ivanov, Ivan T.; Ritter, John (Journal of Corporate Finance, 2015)
We provide evidence that existing studies relating financial condition to product market cooperation produce mixed results because of unique features of the industries examined. In particular, all evidence suggesting that poor financial condition decreases cooperation comes from the airline industry during periods of high idle capacity. Using a unique data set of aggregate airfare hikes and a more recent low-idle-capacity period, we find that poor financial condition is positively associated with product market cooperation. Although financially weak airlines appear to value the immediate cash flows of increased cooperation, only liquidity-constrained firms seem willing to incur the cost of cooperative attempts.